Nurses' Knowledge Of Nursing Care Standards In Inpatient Care Rooms In Health Services In The Work Area Of Community Health Center - Nasution, Nurhafizah; Djunaedi, Djunaedi; Andani, Nur; Peluw, Zulfikar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The Health Center is a Technical Implementation Unit of the District/City Health Service which is responsible for organizing health development in a work area (Kepmenkes RI, 2006). The Health Center is an effort to protect, maintain, and improve the health of the community so as not to interfere with human health and its surroundings. The objectives of nursing care standards are: improving the quality of nursing care, reducing care costs, protecting nurses from negligence in carrying out their duties and protecting patients from non-therapeutic actions. The research method that the researcher used cross-sectional with independent and dependent variables conducted at the same time. This study used instruments in the form of checklist and closed questionnaire. The results showed that 0 respondents' knowledge of nursing care standards was classified as low, 5 (16%) were classified as moderate, and 30 (94%) were classified as high. The conclusion is that the majority of nurses' knowledge of Nursing Care Standards in the inpatient ward of Tanjung Buntung Health Center is in the high category, which is 94%.